2017
DOI: 10.1094/cchem-08-16-0223-r
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Analysis of Historical and Modern Hard Red Spring Wheat Cultivars Based on Parentage and HPLC Analysis of Gluten‐Forming Proteins

Abstract: Cereal Chem. 94(3):560-567Thirty hard red spring (HRS) wheat cultivars released between 1910 and 2013 were analyzed to determine how they cluster in terms of parentage and HPLC analysis of gliadins and unreduced proteins. Markers for reduced height genes were assessed to determine associations between semidwarfism and protein composition, as well as quality characteristics. In terms of parentage, the clusters formed were grouped according to release year and semidwarfism. Farinograph development time and stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…5 To maintain breadmaking quality even as total protein has declined, newer cultivars tend to have more functional protein, which generally means selecting for a predominance of polymeric high MW proteins. 19 In contrast, the low MW proteins, which have variable effects on functional properties of wheat flour, 20 have been mainly responsible for allergenic reactions, 21 which suggests that this fraction may have lower digestibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 To maintain breadmaking quality even as total protein has declined, newer cultivars tend to have more functional protein, which generally means selecting for a predominance of polymeric high MW proteins. 19 In contrast, the low MW proteins, which have variable effects on functional properties of wheat flour, 20 have been mainly responsible for allergenic reactions, 21 which suggests that this fraction may have lower digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other peptides from the ⊍-gliadin and γ-gliadin fractions were also shown to be resistant to digestive enzymes. 23 Malalgoda et al 20 separated gliadin proteins using reverse-phase high-performance liquid chromatography (HPLC) in spring wheats with release years ranging from 1910 to 2013, and found significant differences in protein composition. Subsequently, they quantified immunogenic peptides in the ⊍-gliadin protein fraction and found no relationship to release year.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the no effect of the release year on the protein content in this work is because all samples were grown at the same environmental conditions. Malalgoda, Ohm et al () reported that gliadin protein composition did not undergo changes related to release year in wheat samples. However, there might have been quantitative changes in specific protein components that were associated with the breeding program efforts to improve wheat quality.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, De Santis et al () also found that modern durum wheat showed lower allergenicity than old durum wheat. However, it is important that the gluten indices and protein composition on both historical and modern wheat cultivars should be taken into account for the evaluation of the functional properties of the proteins present in the wheat cultivars (Malalgoda, Ohm et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation